Dynorphin- and enkephalin-like immunoreactivity is altered in limbic- basal ganglia regions of rat brain after repeated electroconvulsive shock - Kanamatsu, T (J Neurosci, 1986)
In an attempt to determine whether the opioid peptides derived from prodynorphin participate in the effects of electroconvulsive shock (ECS), we used radioimmunoassay and immunocytochemistry to measure dynorphin-like immunoreactivity (DN-LI) in various rat brain regions after repeated ECS treatments. Ten daily ECSs caused a significant increase in dynorphin A (1–8)-LI in most limbic-basal ganglia structures, including hypothalamus (50%), striatum (30%), and septum (30%). No significant change was found in the frontal cortex or the neurointermediate lobe of the pituitary. In contrast, 10 ECS treatments depleted DN-LI in hippocampal mossy fibers by 64%. A detailed time- course study revealed that a single shock caused a small but significant increase in hippocampal DN-LI, whereas three consecutive shocks depleted DN-LI by 30%. The maximal decrease in DN-LI was reached after six daily ECSs. The level of DN-LI in the hippocampus partly recovered, but remained lower than the control value 4, 7, and 14 d after the cessation of six daily ECSs (50, 77, and 83% of control value, respectively). In contrast with the ECS-induced depletion of hippocampal dynorphin, 10 daily ECSs caused a significant increase (40%) in (Met5)-enkephalin-LI in the hippocampus, as well as in other limbic-basal ganglia structures. Immunocytochemistry revealed that enkephalin-LI was increased in the perforant pathway, which is presynaptic to the dynorphin-containing mossy fiber pathway in the hippocampus. These observations suggest that different mechanisms may regulate these two opioid peptide systems in the hippocampus.(ABSTRACT TRUNCATED AT 250 WORDS)